EFFECTIVENESS OF PRODUCTION IN SOIL CONTAIN DIFFERENT OF HEAVY METAL LEVEL - Adam Marcysiak; Stanisław Szarek (Acta Scientiarum Polonorum. Oeconomia, 2009)
The crops of plant production on soil with higher content of heavy metals were higher than on soil with low content of these metals. The explanation of this phenomena was based of hormesis effect concept. According to this higher content of heavy metals in the soil of the investigated farms may influence on the differentiation of their farming productivity and effectiveness’ level.